Chuyển động tuyệt đối khu vực đứt gẫy Sông Hồng (từ Yên Bái qua Thái Nguyên) theo số liệu đo GPS - Tô, Trần Đình; Công, Dương Chí (Vietnam Journal of Earth Sciences, 2008)
Absolute motion of the Red River fault system area (from Yen Bai to Thai Nguyen) deducted from GPS data